Truck decoration and religious identity: material culture and social function in Pakistan - Elias, Jamal J. (Material religion, 2005)
Truck decoration in Pakistan is a pervasive practice in which virtually all trucks are ornamented with some combination of epigraphic formulae, poetry, repetitive patterns and figural images. Both the images and epigraphic formulae may or may not be religious in nature. The decoration of a truck can signify a great deal about the religious identities of the individuals associated with the culture of truck decoration and, more specifically, how changes in the content and nature of the decoration mirror changes in the role of religion in Pakistani society. This is accomplished through the comparison of the decorative programs of four trucks, three countenancing forms of religious expression that have long histories among the people of Pakistan and in South Asia in general, and a fourth, the movement commonly called Tablighi Jama'at, which has only recently seen expression in the decoration of Pakistani trucks.